Ответ:
- 1/2
Объяснение:
4x^2+x-2=0
4x^2+x=2 | :4
x^2+(1/4x)=1/2
x^2+1/4x+(1/8)^2 = 1/2 + (1/8)^2
-->> тут можно показать ход вычислений, но я записываю кратко
(x+1/8)^2 = 33/64
x+1/8 = +-
/8 (записать нужно как дробь)
x1 = - ![\frac{\sqrt{33}+1 }{8} \frac{\sqrt{33}+1 }{8}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B33%7D%2B1%20%7D%7B8%7D)
х2 = ![\frac{\sqrt{33}-1 }{8} \frac{\sqrt{33}-1 }{8}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B33%7D-1%20%7D%7B8%7D)
х1 * х2 = -
= -
= (дробь сокращается на 32) = - 1/2